Fruit Morphological and Biochemical Characterization of Three Saudi Arabian Date Palm (Phoenix dactylifera L.) Cultivars Grown in District Khairpur, Pakistan - Solangi, Najamuddin; Mushtaque Ahmed Jatoi; Tunio, Nizamuddin; Mirani, Abdul Aziz; Adel Ahmed Abul-Soad; Markhand, Ghulam Sarwar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
In the present study fruit morphological and biochemical characterization of three Saudi Arabian date palm cultivars (Ajwa, Safawi and Ruthana) were carried out, which were cultivated in the district Khairpur, Pakistan. Fruits were collected at four different fruit growth stages (kimri, khalal, rutab and tamar) from fifteen years old trees for morphological (fruit colour, fruit length, fruit diameter, fruit weight, pulp ratio, seed length, seed diameter, seed weight) and biochemical analyses (moisture content, pH, total soluble solids, total sugars, reducing sugars, non-reducing sugars). Results of fruit physical characters showed that significantly highest fruit length (5.5 cm at rutab stage), fruit weight (20.2 g at khalal stage) was observed in cv. Safawi, whereas at khalal stage significantly lowest fruit length (3.4 cm) was observed in cv. Ajwa and fruit weight (13.2 g) was observed in cv. Ruthana. Fruit/pulp ratio (FPR) (90.7%) was higher in the fruits of cv. Ajwa at khalal stage, while at rutab stage FPR (92%) was higher in the fruits of cv. Safawi. Fruits showed significant variations in colour, size and weight from kimri to tamar stage. Biochemical analyses of fruits revealed that highest moisture content (86.2%) was observed in fruits of cv. Ruthana at kimri stage. Total soluble solids (TSS) increased from 8.7% (at kimri stage) to 20.5% (at tamar stage) in cv. Ruthana. pH of the fruits at kimri stage was 3.2 in cv. Ajwa, whereas pH increased to 5.2 in cv. Ruthana at tamar stage. Total sugars (reducing and non-reducing) increased from 7.56% in cv. Ajwa at kimri stage to 69.7% in cv. Safawi at tamar stage as significantly highest values. Findings obtained in the present study described morphological attributes and biochemical constituents of the fruits of three exotic cultivars introduced in climatic conditions of the district Khairpur, Pakistan will open the route and interest of the farmers to introduce other elite date cultivars grown in the world.